IgG4 anti‐infliximab in treated patients: Clinical impact and temporal evolution. Issue 11 (2nd October 2018) - Vultaggio, A.; Nencini, F.; Carraresi, A.; Pratesi, S.; Movérare, R.; Eriksson, C.; Venemalm, L.; Maggi, E.; Matucci, A.
Abstract: Background: Infliximab (IFX) carries potential risk of immunogenicity with the production of anti‐drug antibodies (ADA). ADA may belong to different isotypes and are usually measured by ELISA bridging assay. This test is not designed to detect IgG4 antibodies. The aim was to measure IgG4 anti‐IFX antibodies in a cohort of IFX‐treated patients and to evaluate their relationship with ADA and their clinical impact. Methods: Anti‐drug antibodies were detected using a bridging ELISA in the serum of 222 treated patients with different clinical outcomes to IFX. The same samples were analyzed for IgG4 anti‐IFX antibodies using an experimental ImmunoCAP assay with reduced serum IgG4 background levels. A longitudinal evaluation was performed in a subgroup of 38 patients to define the temporal evolution of IgG4 anti‐IFX. Results: IgG4 anti‐IFX was found in 26.6% of patients. Eighty of 222 patients were ADA+ (36%) and the majority (57/80, 71.3%) had IgG4 anti‐IFX. Two IgG4‐positive but ADA‐negative patients were identified. IgG4 anti‐IFX levels correlated with the serum levels of ADA. IgG4 anti‐IFX was more common in both reactive and nonresponder patients than in tolerant/responder patients. Patients who had experienced IgE‐mediated reactions displayed significantly higher IgG4 anti‐IFX than IgE‐negative reactive patients. The majority of patients tested positive for IgG4 anti‐IFX after the first seven infusions. Conclusions: IgG4 anti‐IFX is common in treated patients and a large part of ADA producing patients produce IgG4 antibodies. The IgG4 anti‐IFX response does not prevent hypersensitivity reactions to IFX and correlates with the IgE anti‐IFX response. Abstract : IgG4 anti‐IFX were measured using an experimental ImmunoCAP ™ assay with reduced serum IgG4 background levels based on a modified IFX ImmunoCAP for research use only. IgG4 anti‐IFX serum levels positively correlate with those of non‐isotype‐specific anti‐drug antibodies (ADA) and ADA+ patients display higher levels of IgG4 anti‐IFX than ADA− patients. IgG4 anti‐IFX are not protective against clinical outcomes since are detectable more frequently in HR and LOR than in tolerant patients.